The effects of aerobic interval training on heart rate recovery after cardiac resynchronization therapy - André, Eduardo Filipe Bento Mesquitela (2017)
Background: Heart failure is characterized by an autonomic nervous system dysfunction which leads to sympathetic overactivation and parasympathetic imbalance, culminating in central and peripheral dysfunction. In advanced HF, cardiac resynchronization therapy (CRT) and exercise training seem toimprove these conditions and result in improved functional and clinical parameters. A growing body of evidence supports the benefits of aerobic interval training (AIT) in other several HF populations, but less is known about its influence on autonomic function. Here we assessed the effects of AIT on the heart rate recovery (HRR), an indicator of parasympathetic activity. All participants had HF with a reduced ejection fraction, and six days before the intervention, underwent cardiac surgery. Our objective was to compare if the additive effect of AIT to CRT could indeed result in improved vagal reactivation, measured by the difference between the peak heart rate and the HRR at one minute (HRR1diff). Methods: Twenty-nine stable patients (aged 68.96 ± 9.92; VEF< 27 ; and a V O2Peak= 15 mL.kg-1.min-1) who were receiving optimal medical treatment, were randomized either to the control group, or the AIT group. The AIT group exercised twice a week, and began each session with a 10 minute warm-up (50-60% of the peak heart rate), followed by four intervals of 2-minutes (90-95% of the peak heart rate) and a 2-minute recovery (60-70% of the peak heart rate). After the first month, the 2-minute intervals were changed to 4-minute intervals and 3-minutes recovery. After cardiopulmonary exercise testing (CPET) to maximal volitional exertion, using the modified Bruce protocol, patients were seated and the HRR was immediately assessed. Results: After the six months of intervention our main effects were significant for V O2Peak (p= .010) and CPET duration (p= .025). Thus, after testing for simple main effects, only the AIT group depicted significant changes in the post-intervention for: V O2Peak (p= .013), CPET duration (p= .020), heart rate reserve (p= .035), peak pulse pressure (p= .036), and the HRR1diff (p= .025). Conclusions: After six months of intervention, the simple main effects suggest that AIT could improve vagal reactivation, assessed through HRR1diff, in patients that underwent CRT and were engaged in optimal medical treatment. Our findings also suggest that differences between groups in exercise capacity could be due to peripheral factors.